PENGARUH MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAAN SISWA KELAS 1 SDN 1 MEKARSARI - Alawiyah, Syifa Alawiyah; Gunawan, Dani; Nurkamilah, Siti; Nuriyanti, Risma (IPI Press, 2024)
This study aims to analyze the effect of using Big Book media on the early reading skills of first-grade students at SDN 1 Mekarsari. The research employed a quantitative method with a Quasi-Experimental Design, specifically the Static Group Pretest-Posttest Design. This study was conducted to address the issue of low early reading skills among students, including difficulties in recognizing letters, spelling, and understanding texts. Before the use of Big Book media, the reading abilities of students in the experimental and control classes were relatively similar. However, after using Big Book media, the students' reading abilities significantly improved. The findings indicate that Big Book media is not only effective in enhancing early reading skills but also increases students' engagement and enthusiasm in learning. With its visually appealing approach, Big Book motivates students and creates an enjoyable learning environment, resulting in more optimal improvements in their reading abilities.